Identification of the productivity-limiting nutrients of Xuxiang kiwifruit (Actiniadia chinensis) in China’s central Shaanxi province by analyzing soil fertility and leaf elements - WANG, N N; CHEN, Y L; LIU, B; YU, H Y; HAO, Y; HE, H H; LIU, Z D; MA, F W (The Indian Journal of Agricultural Sciences, 2019)
A survey was initiated to identify the productivity-limiting nutrients of Xuxiang kiwifruit (Actiniadia chinensis Lindl.) orchards in central Shaanxi province in China during 2016-2017. For this purpose 149 kiwifruit orchards were selected for leaf sampling and 59 of them were randomly selected for soil analysis. These investigated orchards were divided into two subpopulations: high-productivity subpopulation (21 orchards) and low-productivity subpopulation (128 orchards) according to the fruit yield and appearance as well as vine growth performance. The nutrient concentrations in leaves of high-productivity subpopulation were used to compute the norms of the diagnosis and recommendation integrated system (DRIS), and in low-productivity orchards the order of nutrient requirement was found to be Zn>Mn>K>Fe>Cl>P>B>Ca>Mg>Cu>N. Among them, the deficient nutrients were Zn, Mn and K, while the excessive ones were N, Cu and Mg. However, the limiting elements in various locations and orchard ages differed. These results obtained from leaf analysis were further validated by soil fertility evaluation using sufficiency range, 94.9%, 83.1%, 76.3%, 32.2% and 23.7% of the orchards were high in pH, Ca, Mg, nitrate N and Cu respectively. By contrast, approximately 70% of the soils were low in Fe, Mn, Zn and Cl, and over 30% low in K, P and OM. Results obtained could be used for guiding the sustainably-integrated nutrient management for kiwifruit orchards in central Shaanxi and other regions with similar environmental conditions.